The Model of Muslim-Christian Dialogue in the Hijra to Abyssinia - Gun Gun Gunawan (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2026)
This study examines the model of Islamic-Christian dialogue that emerged during the Hijra to Abyssinia (615 CE), a pivotal yet understudied episode in early Islamic history. Despite extensive scholarship on Muslim-Christian relations in medieval and modern contexts, the Hijra to Abyssinia as a specific locus of interreligious dialogue has received insufficient analytical attention. Prior studies, such as those by Goddard (2000) and Ahmed (1992), have addressed the historical background of Muslim-Christian encounters in general terms but have not systematically analyzed the dialogical model operative in this event. This study addresses that research gap by applying the typology of interreligious dialogue, particularly the inclusivist-pluralist framework, to the primary historical narratives documented in Ibn Hisham’s Sirat Rasul Allah and Al-Mubarakfuri’s Al-Rahiq Al-Makhtum. A qualitative methodology with a historical-hermeneutical approach was employed, involving four stages: source collection, source criticism (heuristik and kritik), interpretation (interpretasi), and historiographical writing (historiografi). The findings reveal that the encounter between Jafar ibn Abi Talib and King Negus constitutes a sophisticated theological dialogue characterized by three distinct phases: confrontation, theological clarification, and mutual recognition. This study proposes the Abrahamic Encounter Framework as a new analytical category in interreligious dialogue theory demonstrating, through retroactive application of contemporary theory to a seventh-century CE event, that the inclusivist-pluralist model was not merely a modern discursive invention but was already operative in the foundational history of Islam. This finding has concrete practical implications: contemporary Muslim-Christian dialogue initiatives can draw upon this historically grounded Abrahamic Encounter Framework as a prescriptive model for conflict resolution and peacebuilding in pluralistic societies.